Spiritual Arts in Ghazals (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the intricate use of poetic devices in classical ghazals, emphasizing the transformative power of istiora (metaphor) and its superiority over tashbeh (simile). By analyzing key couplets, the study highlights how poets employ artistic techniques like hyperbole, personification, and metaphor to depict the intense emotions of love, separation, and despair. The repetitive refrain “yig‘ladi” (wept) serves as a central motif to express the lover's anguish, which is vividly portrayed through lyrical imagery and aesthetic finesse. These stylistic choices not only enhance the emotional depth of the ghazals but also render them timeless expressions of human vulnerability and artistic beauty. The article concludes by reaffirming the enduring appeal of ghazals in capturing universal themes with unparalleled poetic mastery.